The Legal Position and Legal Implications of Siri (Unregistered) Marriage Following the Enactment of Law Number 1 of 2023 (New Penal Code): A Review from the Perspective of Maqashid Syari’ah - Aldi Adriyansyah; Hambari; Syarifah Gustiawati Mukri (JURNAL ILMU SYARIAH, 2026)
This study examines the legal position and legal implications of siri (unregistered) marriage from the perspective of fiqh munakahat and Article 403 of Law Number 1 of 2023 on the Criminal Code. It is motivated by the persistence of siri marriage practices in Indonesian society despite the divergence between Islamic law and positive law in regulating marriage registration. The study aims to describe the legal status of siri marriage and analyze the legal consequences it entails under both legal systems. A qualitative approach combining library research and field study was applied, using normative-juridical and empirical approaches. Primary data were drawn from classical and contemporary fiqh literature, Law Number 1 of 2023, the 1974 Marriage Law, and the Compilation of Islamic Law, while secondary data were obtained through in-depth interviews with a marriage registrar (penghulu) at the Cibinong Religious Affairs Office and an Islamic scholar (kyai). Data were analyzed using the Miles and Huberman model, with data reduction, categorization, comparison, and conclusion drawing. The findings show that siri marriage, which fulfills the pillars and conditions of marriage, is valid under fiqh munakahat, yet marriage registration is regarded as obligatory on the basis of maslahah mursalah and the legal maxim mā lā yatimmu al-wājib illā bihi fahuwa wājib, in order to safeguard justice, lineage, and family rights. Under Article 403 of Law Number 1 of 2023, siri marriage has no civil legal standing because it is not registered with the competent authority, and it may give rise to criminal liability only when it involves concealment of a lawful marriage impediment, under a complaint-based (delik aduan) mechanism. The legal implications include weakened protections for wives and children, administrative difficulties, and uncertainty regarding civil rights, such as inheritance and birth registration. Keywords: Fiqh Munakahat; Legal Implications; Legal Position; Law Number 1 of 2023; Siri Marriage